Pendekatan Bimbingan dan Konseling dalam Mengatasi Pelanggaran "Pamali" di Kampung Pulo Berbasis Kearifan Lokal - Mulyana, Citta Lena Putri; Mubarokah, Rina; Latifah, Kanya; Salsabila, Intan; Asyifa, Firyal Khansa; Supriatna, Mamat (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
This research explores the “Pamali” cultural practices of the indigenous community in Kampung Pulo, Garut, West Java as a form of internal control. A phenomenological approach was employed by involving traditional leaders (Pak Kuncen) and community members as informants. Five main “Pamali” were identified, reflecting the community's philosophy of life (simplicity, togetherness, love of nature, spirituality, and honesty). The community adheres to these “Pamali” in their daily activities, with Pak Kuncen and fellow members reminding one another of their importance. Regular community gatherings serve as a forum for mutual reminders and resolving issues related to “Pamali” violations. Adherence to these “Pamali” has an impact on the sustainability of the indigenous community in Kampung Pulo. Therefore, a guidance and counseling approach that integrates local cultural values is needed to address “Pamali” violations and maintain traditions in Kampung Pulo.